Desain Prototype Sales Report Online Menggunakan Konsep Smart Application Pada PT Evergreen Sentosa - Handayani, Indri; Aini, Qurotul; Kristanti, Citra Yulian (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
The development of today technology evolving so rapidly, especially in industry. Competition in the industry is getting tighter so that the company will always strive to continue to be first in satisfying consumers and that consumers do not switch to another. Information systems sales report is needed by the company to know at any time the sales summary, sales growth can be monitored at any time and are still manually input method can be done in computerized to avoid many mistakes. Recapitulation of sales at PT. Evergreen Sentosa in Tangerang previously used in the bookkeeping and input using Microsoft Excel 2007. The main purpose of the research conducted by the authors is to assist the Company in the sales summary in order to avoid many mistakes, change a system that is still done manually into a computerized online by using the Other: direct observation, conducting interviews with stakeholders, studying the data that has been given from PT. Evergreen Sentosa in Tangerang, and the method of literature done by seeking additional information from a variety of books obtained, analyzed in the form of the Unified Modeling Language (UML) using visual software design paradigm 6.4 and made proposals as you wish stakeholders. From the observations made by the author, the authors obtain results or conclusions that the information system sales reports beneficial to the Company. Keywords: Sales Report , PT . Evergreen Sentosa , UML